2018
DOI: 10.1073/pnas.1808066115
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic regulation and glucose sensitivity of cortical radial glial cells

Abstract: The primary stem cells of the cerebral cortex are the radial glial cells (RGCs), and disturbances in their operation lead to myriad brain disorders in all mammals from mice to humans. Here, we found in mice that maternal gestational obesity and hyperglycemia can impair the maturation of RGC fibers and delay cortical neurogenesis. To investigate potential mechanisms, we used optogenetic live-imaging approaches in embryonic cortical slices. We found that Ca signaling regulates mitochondrial transport and is cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…An ex vivo study by Rash et al (2018) reported impaired RG migratory scaffolding under high glucose environmental due to disruption of RG mitochondrial function or Ca 2+ transport in the RG fibers. Cell migration is an essential mechanism for cortical lamination and function, and the protein Reelin is FIGURE 5 | Current/voltage relationship in deep cortical primary motor cortex neurons of 21-days-old offspring from control and diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…An ex vivo study by Rash et al (2018) reported impaired RG migratory scaffolding under high glucose environmental due to disruption of RG mitochondrial function or Ca 2+ transport in the RG fibers. Cell migration is an essential mechanism for cortical lamination and function, and the protein Reelin is FIGURE 5 | Current/voltage relationship in deep cortical primary motor cortex neurons of 21-days-old offspring from control and diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian neocortex (forebrain-derived telencephalic region) is defined by six layers of neurons generated from a single layer of proliferating progenitor cells (neuroepithelial cells) that become highly polarized at their apicobasal axis (Breunig et al, 2011). This progenitor population, called radial glial cells (RGCs, also known as the primary neural stem cells (NSCs) of the CNS; Rakic, 2009; Rash et al, 2018), initially (E10.5–E12.5) undergoes extensive symmetric divisions to expand, followed by differentiation into neurons or basal progenitors (BPs; Tbr2+, E12.5 onwards; Paridaen and Huttner, 2014; Figure 1A). They later undergo final symmetric divisions to also generate pyramidal neurons (Martínez-Cerdeño et al, 2006).…”
Section: Concomitant Development Of the Neural And Vascular Compartmementioning
confidence: 99%
“…Altering ALDOA dosage in the developing brain will likely impact energy metabolism by altering the flow of metabolites through the glycolytic pathway and impacting subsequent pathways which feed on outputs of glycolysis. Disruption to energy metabolism during development has previously been linked to ASD and ADHD (Rash et al 2018). The offspring of hyperglycaemic mice presented microcephaly, a phenocopy of the microcephaly observed in 16p11.2 microduplication patients (Rash et al 2018) and disruptions to energy metabolism may contribute to the microcephaly seen in the offspring of Zika infected mothers (Gilbert-Jaramillo et al 2019).…”
Section: Aldoamentioning
confidence: 95%
“…Disruption to energy metabolism during development has previously been linked to ASD and ADHD (Rash et al 2018). The offspring of hyperglycaemic mice presented microcephaly, a phenocopy of the microcephaly observed in 16p11.2 microduplication patients (Rash et al 2018) and disruptions to energy metabolism may contribute to the microcephaly seen in the offspring of Zika infected mothers (Gilbert-Jaramillo et al 2019). No homozygous null ALDOA patients have been identified suggesting it is essential for life, but patients with changes to ALDOA levels have been identified; one patient with reduced ALDOA activity presented microcephaly (Kreuder et al 1996) and another presented intellectual disability (Beutler et al 1973).…”
Section: Aldoamentioning
confidence: 99%